COMPARATIVE ANALYSIS OF GOVERNMENT REGULATION OF BUSINESS IN FINLAND, RUSSIA AND GERMANY - Poltavchenko, Alexander (My University, 2016)
New, modern and old conservative business sectors are facing the problem of cooperating with public authorities. Modern world always brings new challenges, where government should balance between supporting the business and competition and caring about citizens by protecting them with different laws. Three chosen countries represent different attitude of business towards government and its regulation. All of these countries have different culture and background, different ways of doing business. That is why their comparison might give a good understanding of this phenomenon. It should be also mentioned, that idea of regulation is strongly connected with the concept of trust. Because building trust between business and government is one of the main conditions for normal functioning of all processes in the country. The main goal of this paper is to compare and analyze political, economic and social situations in Germany, Russia and Finland. Talking about the research problem it is important to notice, that it is impossible to suggest one type of regulation fitting for all the countries. It is very important to find the suitable balance between the regulation and freedom in government – business relations. Thus, it is necessary to study what solution would be better for every particular country. In this work there were studied 2 main concepts – Regulation and Trust. Phenomenon of regulation attempts to understand, what the idea of regulation is and what kind of ways are there to explain it. In addition 5 main purposes of regulation and all global approaches to understand it are identified. The concept of trust was studied in this work as well. It is very wide phenomenon and it has been studied for a long time by different sciences. Trust can be called one the most important topics in sociology. In these frameworks it was examined by such scientists as Francis Fukuyama, Anthony Giddens, Sztompka, Simmel and Garfinkel. Giddens and Toennis were considering trust from economical point of view, trying to understand it on a personal level. These two approaches together with economical approach will be examined in this Thesis work. To provide the data for the empirical research of this work the method of expert interview was chosen. To summarize the results it is possible to say that all of the respondents agreed that today the situation in political, economical and social life is very special – many different crises and other problems. However it is hard for all of the respondents to say that regulations are too strong for this time. Of course, some of them are quite tough and probably not necessary, but at the same time in all of the countries government is trying to help business with ‘positive’ regulation and such help is not considered as extensive.
Keywords: Regulation; trust; control; business regulation; governance; public management.; fi=Julkisjohtaminen|en=Public Management |; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|